The insecurity state vulnerable autonomy and the right to security in the criminal law - Ramsay, Peter (Oxford : Oxford University Press, 2012)
This text analyses the anti-social behaviour order and demonstrates that orders impose a liability on those who fail to reassure others about their future security. It traces the justification of this liability through the conditional character of citizenship in New Labour policy to an underlying concept of vulnerable autonomy.
Series from dust jacket.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nuisances -- Great Britain -- Criminal provisions; Criminal law -- Great Britain